A Developmental Study of Abnormal Behaviors and Altered GABAergic Signaling in the VPA-Treated Rat Model of Autism - Hou, Qianling; Wang, Yan; Li, Yingbo; Chen, Di; Yang, Feng; Wang, Shali (Frontiers in Behavioral Neuroscience, 2018)
Although studies have investigated the role of GABAergic signaling in rodent neural development and behaviors relevant to autism, behavioral ontogeny, as underlainie by the changes in GABAergic system, are is poorly characterized in different brain regions. Here we employed a VPA rat model of autism to investigate the autism-like behaviors and GABAergic GAD67 expression underlying these altered behaviors in multiple brain areas at different developmental stages from birth to adulthood. We found that VPA-treated rats exhibited behavioral abnormalities relevant to autism, including delayed nervous reflex development, altered motor coordination, delayed sensory development, autistic-like and anxiety behaviors, and impaired spatial learning and memory. We also found that VPA rats had the decreased expression of GAD67 in the hippocampus and cerebellum from childhood to adulthood, while decreased GAD67 expression of the temporal cortex was only observed in adulthood. Conversely, GAD67 expression was increased in the prefrontal cortex from adolescence to adulthood. The Prenatal VPA exposure dysregulated GAD67 expression and could alter the excitatory-inhibitory balance in the cerebral cortex, hippocampus and cerebellum. Our findings indicate an impaired GABAergic system could be a major etiological factor occurringed in the cerebral cortex, hippocampus and cerebellum in of human cases of autism, which could direct towards tosuggests enhancement of GABA signaling as would be a promising therapeutic strategy target for the its treatment of autism.